Free Veno - Venous Graft.: Indications, Technique and Res.ults (an eleven - Year Experience) - Danza, Rómulo; Navarro, Teodoro; Baldizán, Jorge; Olivera, Daniel (Cirugía del Uruguay, 1980)
By - pass in venous sector has fewer indications than at arterial level but, if faced with the serious probiems entailed by the acute or chronic interruption of the large venous trunks in the limbs, and when there is risk of life or function of limb, free veno· - venous by - pass should be considered.